2018
DOI: 10.56093/ijas.v88i4.79104
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of combining ability and heterosis for yield and yield attributing traits in Indian mustard (Brassica juncea)

Abstract: Indian mustard [Brassica juncea (L) Czern. and Coss.] is an important oilseed crop which occupies leading position in oilseed sector of Indian agriculture. Development of high yielding genotypes with high oil content in Indian mustard has been a major breeding objective owing to high edible oil import in India. Present study was conducted with a set of 53 genotypes, that included 40 crosses and 13 parents evaluated for pooled estimation of combining ability and heterosis for yield and yield attributing traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…All the traits except plant height and primary branching exerted high extent of positive indirect effects on seed yield per plant via harvest index in both E1 and E2 conditions i.e., biological yield per plant (0.4150 and 0.2284), number seeds per siliqua (0.3789 and 0.3324), secondary branching (0.3435 and 0.3093), no. of silique on main raceme (0.3324 and 0.3346), length of main raceme (0.3046 and 0.2714), days to maturity (0.2140 and 0.1620), 1000-seeds weight (0.2125 and 0.1887), and days to 50% flowering (0.1965 and 0.2292), Similar finding were reported by Yadava et al (2012) [21] , Yohannes and Belete (2013) [22] , Singh et al (2013) [14] , Lodhi et al (2014) [5] , Shekhawat et al (2014) [13] , Tahira et al (2015) [18] , Dipti et al (2016) [3] , Singh et al (2017) [16] , Rauf and Rahim (2018) [9] , Nur-E-Nabi et al (2019) [7] and Tripathi et al (2020) [19] . At phenotypic level, the highest positive direct effect on seed yield/plant was exerted by harvest index (0.8102 and 0.8463 respectively) followed by biological yield per plant (0.4382 and 0.4529) respectively in E1 and E2 conditions.…”
Section: Path Coefficient Analysis: Investigating Direct and Indirect...supporting
confidence: 87%
“…All the traits except plant height and primary branching exerted high extent of positive indirect effects on seed yield per plant via harvest index in both E1 and E2 conditions i.e., biological yield per plant (0.4150 and 0.2284), number seeds per siliqua (0.3789 and 0.3324), secondary branching (0.3435 and 0.3093), no. of silique on main raceme (0.3324 and 0.3346), length of main raceme (0.3046 and 0.2714), days to maturity (0.2140 and 0.1620), 1000-seeds weight (0.2125 and 0.1887), and days to 50% flowering (0.1965 and 0.2292), Similar finding were reported by Yadava et al (2012) [21] , Yohannes and Belete (2013) [22] , Singh et al (2013) [14] , Lodhi et al (2014) [5] , Shekhawat et al (2014) [13] , Tahira et al (2015) [18] , Dipti et al (2016) [3] , Singh et al (2017) [16] , Rauf and Rahim (2018) [9] , Nur-E-Nabi et al (2019) [7] and Tripathi et al (2020) [19] . At phenotypic level, the highest positive direct effect on seed yield/plant was exerted by harvest index (0.8102 and 0.8463 respectively) followed by biological yield per plant (0.4382 and 0.4529) respectively in E1 and E2 conditions.…”
Section: Path Coefficient Analysis: Investigating Direct and Indirect...supporting
confidence: 87%
“…The strong negative correlation between these two traits may be due to strong linkage between the genes controlling oil and glucosinolate content of seeds. Priyamedha et al (2018) also reported negative correlation between these two traits.…”
Section: Discussionmentioning
confidence: 88%
“…Secondly, a robust system for producing a large quantity of hybrid seeds must be in place. Lastly, an effective method for identifying hybrids with exceptional combining ability is essential [56,57].…”
Section: Heterosis Breedingmentioning
confidence: 99%